LRP6-mediated phosphorylation of connexin43 in myocardial infarction - Xu-min Zhang; Ya-ling Liu; Ying Cai; Ying Hao; Sheng Kang (iScience, 2023)
Summary: Ventricular tachycardia (VT) and ventricular fibrillation are most causes of early death in patients with acute myocardial infarction (AMI). Conditional cardiac-specific low-density lipoprotein receptor-related protein 6 (LRP6)-knockout mice with connexin 43 (Cx43) reduction triggered the lethal ventricular arrhythmias. Thus, it is necessary for exploring whether LRP6 and its upstream genes circRNA1615 mediate the phosphorylation of Cx43 in VT of AMI. Here, we showed that circRNA1615 regulated the expression of LRP6 mRNA through sponge adsorption of miR-152-3p. Importantly, LRP6 interference fragments aggravated hypoxia injury of Cx43, while overexpression of LRP6 improved the phosphorylation of Cx43. Subsequently, interference with G-protein alpha subunit (Gαs) downstream of LRP6 further inhibited the phosphorylation of Cx43, along with increasing VT. Our results demonstrated that LRP6 upstream genes circRNA1615 controlled the damage effect and VT in AMI, and LRP6 mediated the phosphorylation of Cx43 via Gαs which played a role in VT of AMI.